The business and management of conventions - Poole, Barry.; Weeks, Paul.; Leiper, Neil.; McCabe, Vivienne. (John Wiley and Sons, 2000)
This book is about: The business environment of conventions; The business structure of conventions; Managing suppliers to conventions; Managing human resources for conventions; ...